Cellular location and expression of Na+, K+‐ATPase α subunits affect the anti‐proliferative activity of oleandrin. Issue 4 (16th October 2012) - Yang, Peiying; Cartwright, Carrie; Efuet, Ekem; Hamilton, Stanley R.; Wistuba, Ignacio Ivan; Menter, David; Addington, Crandell; Shureiqi, Imad; Newman, Robert A.
Abstract The purpose of this study was to investigate whether intracellular distribution of Na+, K+‐ATPase α3 subunit, a receptor for cardiac glycosides including oleandrin, is differentially altered in cancer versus normal cells and whether this altered distribution can be therapeutically targeted to inhibit cancer cell survival. The cellular distribution of Na+, K+‐ATPase α3 isoform was investigated in paired normal and cancerous mucosa biopsy samples from patients with lung and colorectal cancers by immunohistochemical staining. The effects of oleandrin on α3 subunit intracellular distribution, cell death, proliferation, and EKR phosphorylation were examined in differentiated and undifferentiated human colon cancer CaCO‐2 cells. While Na+, K+‐ATPase α3 isoform was predominantly located near the cytoplasmic membrane in normal human colon and lung epithelia, the expression of this subunit in their paired cancer epithelia was shifted to a peri‐nuclear position in both a qualitative and quantitative manner. Similarly, distribution of α3 isoform was also shifted from a cytoplasmic membrane location in differentiated human colon cancer CaCO‐2 cells to a peri‐nuclear position in undifferentiated CaCO‐2 cells. Intriguingly, oleandrin exerted threefold stronger anti‐proliferative activity in undifferentiated CaCO‐2 cells (IC50, 8.25 nM) than in differentiated CaCO‐2 cells (IC50, >25 nM). Oleandrin (10 to 20 nM) caused an autophagic cell death and altered ERK phosphorylation in undifferentiated but not in differentiated CaCO‐2 cells. These data demonstrate that the intracellular location of Na+, K+‐ATPase α3 isoform is altered in human cancer versus normal cells. These changes in α3 cellular location and abundance may indicate a potential target of opportunity for cancer therapy. © 2012 Wiley Periodicals, Inc.